Panel cointegration analysis and generalized Causality of HYV Boro production of six different districts of Bangladesh. - Shitan, Mahendran; Karmokar, Provash Kumar (2011)
Boro rice of High Yielding Variety (HYV) is cultivated all over the country and has an important role in supplying the food requirements for the inhabitants of Bangladesh. Various researchers have investigated the relationship among some variables by cointegration/multicointegration technique using Dickey Fuller (DF) and Augmented Dickey Fuller (ADF) Unit Root Test within the Error Correction Model (ECM) framework. In view of Im, Pesaran and Shin, panel unit root test is used in the present study, to test the stationarity of the data set of the six districts of Bangladesh. The six districts are Rajshahi, Rangpur, Jessore, Barisal, Mymensingh and Dinajpur. The variables for each of these districts are the yields of Boro rice. We denote these variables as Yraj, Yran, Yjes, Ybar, Ymym and Ydin, respectively for the six districts. Further, Generalized Granger casualty has been judged within the ECM framework. Our study revealed that a cointegrating relationship exist between Yraj and Yran. Further, we also found Generalized Granger Causality from HYV Boro rice production of Rangpur to HYV Boro rice production of Rajshahi within the ECM framework.